Isolation and identification of Murine Mesenchymal Stem Cells from Bone Marrow. - Jabeen , Sehrish; Vohra, Muhammad Sufyan; Raza, Yasir (International Journal of Endorsing Health Science Research, 2022)
Background: Mesenchymal stem cells (MSCs) are beneficial for cell and gene therapy approaches. These cells are highly potent in producing various cells, including adipocytes, osteoblasts, hematopoietic cells, etc., particularly bone marrow-derived. High proliferation and regenerative capacity are important phenotypes of MSCs which contribute to the recovery process at the damaged sites. Various techniques have been used, which have inconvenient effects on stromal cell properties. The present study evaluates the stem cell markers in the isolated cells from the Murine mouse bone marrow. Methodology: The murine mesenchymal stem cells (mMSCs) were isolated from the bone marrow of murine Balb/c mice using a simple in vitro culture protocol. Trypan blue exclusion assay was performed for viable cell count, and cellular morphology was checked using an inverted microscope. The immunofluorescence staining was done to analyze the immunophenotypic features of mMSCs by treating cells with CD44, CD90, and CD45 fluorescent antibodies. Results: mMSCs with spindle-like cell appearance were attained within three weeks. Immunofluorescence staining of isolated mMSCs displayed a statistically significant (p<0.001) number of CD44 and CD90 positive cells. Alternatively, an insignificant count of CD45 labeled cells was found. Conclusion: A uniform mMSC population was achieved with high propagation capability in lower passages through regular replacement of medium and reduced trypsinization time. In addition, mMSCs were strongly expressed MSCs positive markers, including CD44 and CD90.